The effects of zumba and strong by zumba on body fat and circumference in women aged 20–40 - Cahya Allistia, Syahida; Rahayu, Setya; Mukarromah, Siti Baitul; Sumartiningsih, Sri (Universitas Nusantara PGRI Kediri, 2021)
This study aims to analyze the influence and analyze the differences between zumba and strong by zumba exercises limited to body fat and body circumference in women aged 20–40 years. This research method is a study using a quasi-experiment with a control group pretest and posttest design. Data analysis techniques are collected, processed, and analyzed statistically by calculating the average deviation and testing of normality requirements from the score distributor using SPSS version 15.00 for window evaluation. The results of the zumba exercise method had a decrease in the thickness of belly fat by -7.60, a decrease in the thickness of biceps fat of -5.60, and a decreased thickness of triceps fat of -5.30, while the strong by zumba exercise method had a decrease in belly fat thickness of -15.90, a decrease in biceps fat thickness of-9.80, and a decreased thickness of triceps fat of -9.20. The zumba exercise method had a decrease in abdominal circumference of -7.80, a decrease in thigh circumference of -4.20, and a decreased arm circumference of -5.50, while the strong by zumba exercise method had an average decrease in abdominal circumference of -11.40, a decrease in thigh circumference of -3.90, and decreased arm circumference of -7.60. Strong by zumba exercises are more effective for reducing body fat thickness as well as decreasing body circumference, and strong by zumba exercises are more effective for reducing body circumference.